The application of Blog as a teaching media in improving students’ writing - Febianti, Kurnia; Wahyuni, Sri (Indonesian Educational Administration and Leadership Journal (IDEAL), 2019)
The objective of this study is to find out the significant difference of the students in writing achievement before and after applying Blog as a teaching media. Quasi experimental design was used in this study. The population of this study was all 2nd semester of English study program of STKIP Muhammadiyah Pagaralam in academic year 2018/2019. The sample was taken by using purposive sampling technique. The written test was used in collecting the data. The results of the test were analyzed by using t-test through SPSS. The calculation of the independent sample t-test shows that t-obtain was 6.55. The level of significance of (p <.01) in two-tailed testing with df 42. The critical value of t-table was. 2.01. The result of the study showed that there was a significant difference of students’ writing achievement before and after implementing Blog as a teaching media. It can be seen from the analysis of independent score that shows that of t-obtain was higher than t-table (p > 2.01). It can be concluded that Blog could improve students’ writing achievement at STKIP Muhammadiyah Pagar Alam.